2008
DOI: 10.1101/gad.1613608
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic failure in male mice lacking an X-linked factor

Abstract: Meiotic silencing of sex chromosomes may cause their depletion of meiosis-specific genes during evolution. Here, we challenge this hypothesis by reporting the identification of TEX11 as the first X-encoded meiosis-specific factor in mice. TEX11 forms discrete foci on synapsed regions of meiotic chromosomes and appears to be a novel constituent of meiotic nodules involved in recombination. Loss of TEX11 function causes chromosomal asynapsis and reduced crossover formation, leading to elimination of spermatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
192
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(208 citation statements)
references
References 40 publications
11
192
0
1
Order By: Relevance
“…For histology, testes were fixed in Bouin's solution overnight, dehydrated in ethanol, embedded in paraffin, sectioned, and stained with hematoxylin and eosin. Surface-spread analysis of spermatocyte nuclei and immunofluorescence analyses of testis sections were described previously (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For histology, testes were fixed in Bouin's solution overnight, dehydrated in ethanol, embedded in paraffin, sectioned, and stained with hematoxylin and eosin. Surface-spread analysis of spermatocyte nuclei and immunofluorescence analyses of testis sections were described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…V6.5 ES cells were electroporated with linearized Mov10l1 targeting construct (pKe16-1/ClaI). Screening of ES cells was described previously (37). Two ES cell clones (A1 and B10) harboring the Mov10l1 fl allele were injected into B6C3F1 (Taconic) blastocysts.…”
Section: Methodsmentioning
confidence: 99%
“…It regulates homologous chromosome synapsis and double‐strand DNA breakage repair. Thus, it is critical for synaptonemal complex and chiasma formation during chromosomal cross‐over 103, 104, 105, 106. The protein is highly conserved and functionally uniform across species 103.…”
Section: Culprit Genes That Have Been Identified In the X Chromosomementioning
confidence: 99%
“…crossovers, leading to infertility in males. 6 Interestingly, another study reported that the deficiency of Tex11 led to impaired crossover and achiasmate chromosomes at Meiosis I; however, males were fertile. 5 This discrepancy in phenotype could be attributed to the differential efficiency of gene knockout (a null allele vs. a hypomorphic allele), given that only one exon (exon3) was conditionally deleted in the Tex11 knockout animal in the second study.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The TEX11 protein was found to form discrete foci along the synaptonemal complexes (SCs) on meiotic chromosomes and was shown to be essential for meiosis in males. 6 The conditional deletion of 27 exons (out of a total of 30 exons) of Tex11 in mice resulted in defects in synapsis formation and meiotic testis expressed gene 11 (Tex11) is essential for meiosis and male fertility in the mouse. Currently, little is known about the control of spermatogenesis in non-rodent animal models such as pigs.…”
Section: Introductionmentioning
confidence: 99%